PEMANFAATAN TEKNOLOGI KELAUTAN DALAM MENGATASI LIMBAH SAMPAH PLASTIK DI KAWASAN PESISIR PANTAI LOSARI - Suleman, Siti; Pratama, Andhika Hayyu; Mistipa, Fabelyn Gandryal; Ardyansyah, Muhammad Fakhri; Hidayah, Nurul; Pratama, Hans Julio (Riset Sains dan Teknologi Kelautan, 2022)
Waste or garbage is the residue or waste generated from daily activities or activities in social life. Where people live, there various types of waste will be generated. This is also the case in the Losari Beach area, where there are many daily activities that involve interaction in the community, resulting in waste that actually has an impact on the pollution of Losari Beach. Losari Beach is a beach located in the west of Makassar City, South Sulawesi Province, Indonesia. This beach is a place for Makassar residents to spend time in the morning, afternoon and evening enjoying the beautiful view of the sunset. Unfortunately, the beauty of the buildings on the coast is not as beautiful as the dirty sea view filled with plastic waste floating on the beach due to people's behavior of throwing garbage in the sea. The main problem is the lack of public awareness of the cleanliness of their waste, be it plastic waste, beverage bottles, or food or snacks found around Losari Beach which are directly dumped into the sea area. Therefore, there is a need for public awareness of the cleanliness of their waste. With the existence of technology, it will facilitate the work in cleaning up waste that is difficult for humans to do. One example of the application of technology in cleaning up waste is the BeBot robot. The BeBot robot is a robot created to clean up plastic waste on the coast. BeBot has several advantages, namely environmentally friendly, operating without pollution and others.